Enriched environments enhance the development of explicit memory in an incidental learning task - Carina Jaap; Marike C. Maack; Philipp Taesler; Frank Steinicke; Michael Rose (Scientific Reports, 2022)
Abstract Learning, rendered in an implicit (unconscious) or explicit (conscious) way, is a crucial part of our daily life. Different factors, like attention or motivation, influence the transformation from implicit to explicit memory. Via virtual reality a lively and engaging surrounding can be created, whereby motivational processes are assumed to be a vital part of the transition from implicit to explicit memory. In the present study, we tested the impact of an enriched virtual reality compared to two conventional, non-enriched 2D-computer-screen based tasks on implicit to explicit memory transformation, using an audio-visual sequential association task. We hypothesized, that the immersive nature of the VR surrounding enhances the transfer from implicit to explicit memory. Notably, the overall amount of learned sequence pairs were not significantly different between experimental groups, but the degree of awareness was affected by the different settings. However, we observed an increased level of explicitly remembered pairs within the VR group compared to two screen-based groups. This finding clearly demonstrates that a near-natural experimental setting affects the transformation process from implicit to explicit memory.